STRUKTUR DAN FUNGSI CERITA RAKYAT MASYARAKAT MELAYU KECAMATAN SIMPANG HILIR KABUPATEN KAYONG UTARA - Darpid, Darpid; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to find out objectively about the Structure and Function of Malay Folklore of Simpang Hilir District of North Kayong Regency. This research uses a structural approach. The research method used is descriptive with qualitative research forms. The source of this research data is data that comes from speakers. While the data in this study is the folklore "Meriam Bujang Koreng, Riye Rupe, Ujang Mali Budiman". Implementation of research results on Indonesian learning in the form of quotations in the form of words, phrases, clauses, or sentences. The results of research into folklore are as follows. First, the character and characterization in folklore. Both events take place in folklore. The three lines in folklore. The four mandates contained in folklore. The fifth describes the function of folklore for people's lives. In addition, the results of this study can also be used as learning materials for even-sized X classes in the 2013 curriculum. With Basic Basic Competence (KD) 3.7 Identify the values and content contained in folklore (hikyat) both oral and written. 4.7 Retelling the contents of folklore (hikayata) heard or read.